Study of Patients’ awareness and their perspective about diabetic disorder in T2DM patients: A descriptive study - Bhardwaj, RAJ Kumar; Kazal, H L; Kohli, Kamlesh; Panag, KMDS; Paul, Kavita (Journal of Drug Delivery and Therapeutics, 2019)
Introduction: Type 2 Diabetes mellitus, a metabolic disorder is mostly related to the sedentary life style of subjects. Awareness of diabetes disorder among diabetics plays a crucial role in its management.Aims & Objectives: To study the awareness of diabetes disorder, its complications and management among T2DM patients.Materials and Methods: This was a cross-sectional and descriptive study done among T2DM patients who visited the OPD of department of Medicine at GGS Hospital, Faridkot (in a rural area of Punjab-India). A pretested proforma contained questionnaire related to the awareness/ knowledge to diabetic disorders, its complications and management was distributed among 300 subjects and their response was analyzed.Results: 235 patients responded (78.33%) to the pretested proforma. Males and females were 48.08% and 51.92% respectively. 25.53% subjects were illiterate. Lack of knowledge about diabetic disorders in 79.57%, duration of treatment in 73.61%, their complications in 74.89%, modification of diet in 40%, their body care/cleanliness in 62.55% and leaving of medication in 76.17% were seen. A habit of taking other indigenous / complimentary medicines was also seen in 40.43% of cases along with conventional antidiabetic therapy.Conclusion: Most of the diabetic patients had lack of knowledge about diabetic disorders, its complications and management. They also left the medicine in midway of treatment and had developed signs & symptoms of hyperglycemia. A good number of patients also took indigenous products to treat their disease. They also didn’t follow the life style modification measures appropriately. Therefore, adequate awareness/knowledge should be provided to all the diabetic patients to manage diabetic disorder in a better way.Keywords: Knowledge, Perspectives, Complications, Life style modification, Complementary & Alternative medicine (CAM), Medication compliance & Adherence.